2009
DOI: 10.1021/pr800840x
|View full text |Cite
|
Sign up to set email alerts
|

Ran GTPase Regulates Hemocytic Phagocytosis of Shrimp by Interaction with Myosin

Abstract: Ran GTPases, one family of small G protein superfamily, have been widely demonstrated to be involved in the transport system between cytoplasm and the nucleus. However, the function of Ran GTPase in immunity remains unclear. In our study, it was found that the Ran GTPase (designated as PjRan) was up-regulated in virus-resistant shrimp, indicating that the PjRan might be implicated in the innate immune system against virus infection. On the basis of protein interactions, it was found that the PjRan interacted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 35 publications
2
80
0
Order By: Relevance
“…To ensure that the shrimp were WSSV-free before the experiments, three shrimp were randomly selected for WSSV detection by use of WSSVspecific primers (5=-TTGGTTTCATGCCCGAGATT-3= and 5=-CCTTG GTCAGCCCCTTGA-3=). The virus-free shrimp were challenged with WSSV as described previously (16). Briefly, the tissues of WSSV-infected shrimp were homogenized in TN buffer (20 mM Tris-HCl, 400 mM NaCl, pH 7.4) at 0.1 g/ml.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure that the shrimp were WSSV-free before the experiments, three shrimp were randomly selected for WSSV detection by use of WSSVspecific primers (5=-TTGGTTTCATGCCCGAGATT-3= and 5=-CCTTG GTCAGCCCCTTGA-3=). The virus-free shrimp were challenged with WSSV as described previously (16). Briefly, the tissues of WSSV-infected shrimp were homogenized in TN buffer (20 mM Tris-HCl, 400 mM NaCl, pH 7.4) at 0.1 g/ml.…”
Section: Methodsmentioning
confidence: 99%
“…To analyze the expression of the shrimp caspase 8 gene, quantitative real-time PCR was conducted as described previously (16). Shrimp ␤-actin was used as a control.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…These viruses employ Cdc42-hijacking tactics in their target cell entry processes (14). Some GTPases show antiviral functions by interacting with actin in shrimp; for example, the GTPase Rab6 interacts with actin to regulate phagocytosis in Marsupenaeus japonicus hemocytes (15), and the GTPase Ran is involved in the hemocytic phagocytosis of white spot syndrome virus (WSSV) through its interaction with myosin (16). Rac1, the other member of the Rho family, plays a role in the antiviral and antibacterial innate immunity of shrimp (17).…”
mentioning
confidence: 99%
“…Some documents indicated that small GTPases are related to virus infection in the shrimp (Wu et al 2007;Liu et al 2009;Zhang et al 2010). Also, the small GTPases of zebra fish have provided a firm basis of an innate immune system in vertebrates (Salas-Vidal et al 2005).…”
Section: Introductionmentioning
confidence: 99%